Penerapan Metode Simpang Tegar untuk Meningkatkan Kemampuan Guru dalam Penulisan PTK dan Artikel Ilmiah - I Wayan Widana; I Made Suarta; I Wayan Citrawan (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
The ability of SMAN 1 Selemadeg and SMAN 1 Kerambitan, Tabanan Regency, Bali Province teachers, in writing Classrom Action Research (CAR) reports and articles is very low. This problem has an impact on the delay of the promotion of teachers for many years, because one of the requirements is not fulfilled in the element of scientific papers. Community service aims to improve the ability of teachers in writing CAR and articles. To achieve these objectives, the Simpang Tegar method is implemented. Data on teacher understanding of the basic concepts of CAR and articles were collected using the test method. While the data on the skills of teachers writing CAR and articles are collected using observation and check-list of tasks given during mentoring. The results obtained are as follows: (1) teacher's understanding of the basic concepts of CAR and scientific articles increased from an average of 57.34 during the pre-test to 73.93 during the post-test; (2) teacher's skills of writing CAR reports and articles increased from an average of 45.41 before mentoring, to 68.58 after mentoring